Trust on a Swipe: Exploring the Role of Impulsiveness and Virtual Transactions in Purchasing Intentions - Setyaning, Alldila Nadhira Ayu (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the impact of virtual transaction systems and impulsive buying on trust and how this trust influences the purchasing intentions among Indonesian consumers. Using a quantitative approach and SEM-PLS analysis with 247 respondents, the research findings indicate that virtual transaction systems and impulsive buying both have a positive and significant impact on trust. Moreover, trust is shown to positively and significantly affect purchasing intentions. Additionally, trust is found to mediate the relationship between virtual transaction systems and purchasing intentions, as well as the relationship between impulsive buying and purchasing intentions. The results provide valuable insights for e-commerce platforms to refine their payment options and customer engagement strategies to build a more trustworthy and seamless shopping experience.